A survey of panties used by pregnant women in their third trimester of pregnancy - Cadiz, Flor Ghizelle B.; Elumba, Patricia Santos (2005.)
In the Philippines, 2.3 million women in the reproductive age group are expected to get pregnant. Of these, two million will deliver. The maternity panties available in the local market are limited in styles. Pregnant women choose underwear based on their special needs such as physiological change, comfort and support. The study is conducted to determine the attributes of a maternity panty which will guide the manufacturer in its design and construction. In order to realize the study, one hundred (100) pregnant women from four Quezon City hospitals were asked to answer the questionnaires. The respondents were in their third trimester of pregnancy as they could relate to all the changes in the whole duration of pregnancy. With the one-hundred questionnaires given out, only sixty were answered and returned, and of the sixty, only forty qualified for the purpose of the study. The study first determined the kind of panties used by pregnant women. The considerations in panty selection were also asked. The study then analyzed what attributes of a maternity panty are needed to meet the needs of pregnant women. Subsequently, the study recommended maternity panty guidelines for panties that should prove helpful to both mother and manufacturer. Majority of the respondents (50%) use regular size of panties in the first trimester and oversized panties on the second (32.5%) and third trimesters (47.5%). The brief panty is the most preferred style by pregnant women (30%), followed by bikini (27.5%), hikini (20%), and "pouch-like" panty (12.5%). The major considerations in the selection of panty are cost having the most number of responses (12), followed by physiological change (11) and material (11), cut (10) and color (10). Thin and wide elastics that will not constrict the waist and wide leg openings are preferred. Pregnant women also want fabrics to be comfortable, soft, and easy to wash. Panties for the first trimester should have thick and absorbent crotch. For the second and third trimester, thick and absorbent crotch, wide leg opening, waistline expansion and support are suggested. Increase in waistline measurements requires options in elastics, drawstrings, buttons on openings and width of waistband. Options in providing gathering in front waistband and pouch-like front could also be applied for the growth in the abdomen. Elastics on the waist should be thin and wide and should fit comfortably. Leg opening of panty should be increased fro greater movement. Designs should be attractive, easy to wear and can be worn with minimum need to bend over. The researcher recommends further research on the comparison of designs appropriate for pregnant women. An experimental research should also be conducted where a prototype of a developed design can be tested for its applicability. Finally, a study on the evaluation of different styles should also be performed.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Lingerie; Underwear